Low Risk of Central Nervous System Relapse Among Patients With T‐Cell/Histiocyte‐Rich Large B‐Cell Lymphoma Despite High‐Risk Disease Presentation - Karhu, Atte; Aronen, Sara; Rönkä, Aino; Sunela, Kaisa; Klaavuniemi, Tuula; Aromaa‐Häyhä, Annikki; Kuusisto, Milla; Jokelainen, Otto; Böhm, Jan; Vuolukka, Kristiina; Arkko, Ulla‐Mari; Vaittinen, Samuli; et al. (Wiley, 2026)
T-cell/histiocyte-rich large B-cell lymphoma (THRLBCL) is a rare subtype of large B-cell lymphoma (LBCL) for which central nervous system (CNS) relapse remains a devastating complication. The CNS International Prognostic Index (IPI) is usually used to predict the risk of CNS relapse. However, the overall risk of CNS relapse among patients with THRLBCL remains poorly known. To clarify the risk of CNS relapse in THRLBCL, data for 106 patients with THRLBCL diagnosed between 2000 and 2020 were collected from seven hospitals throughout Finland. The control data consisted of 660 patients with diffuse LBCL (DLBCL) diagnosed and treated in Oulu University Hospital. Most of the patients with THRLBCL and DLBCL presented with advanced stage disease and were classified as high-intermediate or high-risk groups based on their IPI score. 368 patients received R-CHOP as first line therapy. Our data included patients who had received CNS prophylaxis. For the entire patient population, we found a 5-year CNS relapse risk of 1.04% and 5.29% among patients with THRLBCL and DLBCL, respectively (p < 0.001). In conclusion, THRLBCL has lowered CNS relapse risk compared to DLBCL.